Evaluation Of Refractive Error And Vision Related Problems Among Children In Rural Area - . E, Mageshwaran; Muralitharan. N, Muralitharan. N; . V, Aarthi; Sowmya. E, Sowmya. E; Preethika. D, Preethika. D; Manikandan. B, Manikandan. B; Kiran Kumar, Allavari; Priyadharshini. S, Priyadharshini. S; Priyasi. D, Sherlin (Journal of Neonatal Surgery, 2025)
Background: Refractive error is a common eye condition that occurs when eye shape prevents light from focusing directly on the back of eye, resulting in blurry vision. It is one of the leading cause for visual impairment in children. Convergence insufficiency and excess accommodation insufficiency and excess, colour vision deficiency, extraocular muscle weakness, squint, visual field defect can cause severe impact in children vision. Objective: To evaluate the refractive status of eye and vision related problems like accommodation excess, accommodation insufficiency and convergence insufficiency using RAF (Royal Air Force Rule) and colour vision deficiency, EOM weakness, corneal reflex, and visual field defect in children in rural area. Methods: In the period between February 2023 to April 2023 all the study participants underwent vision screening in rural area school Chidambaram, India. Visual acuity is measured for both distance and near, NPC and NPA is measured using RAF ruler, corneal reflex is assessed using pen torch, EOM motility tested by broad h test, colour vision is measured using Ishihara plates and visual field is assessed using amsler grid chart test and confrontation field test. Result: This study includes 500 participants between the age group of 8 -16 years, with a mean age of 12.6 ± 2.02 years;278(55.6%) were male children and 222(44.4%) were female children. A total of 149 (29.8%) of uncorrected refractive error, 11(2.2%) of colour vision defect, 401(80.2%) of accommodation excess and 7(1.4%) of accommodation insufficiency, 20(4.0%) of convergence insufficiency, 51(10.2%) of exophoria, 42(8.4%) of EOM problems, 9(1.8%) of visual field defect was seen in children. Conclusion: High prevalence of uncorrected refractive error and vision related problems are present in children.